Assessment of SOLPS5.0 divertor solutions with drifts and currents against L-mode experiments in ASDEX Upgrade and JET. (19th January 2017) - Aho-Mantila, L; Potzel, S; Coster, D P; Wischmeier, M; Brix, M; Fischer, R; Marsen, S; Meigs, A; Müller, H W; Scarabosio, A; Stamp, M F; Brezinsek, S
Abstract: The divertor solutions obtained with the plasma edge modelling tool SOLPS5.0 are discussed. The code results are benchmarked against carefully analysed L-mode discharges at various density levels with and without impurity seeding in the full-metal tokamaks ASDEX Upgrade and JET. The role of the cross-field drifts and currents in the solutions is analysed in detail, and the improvements achieved by fully activating the drift and current terms in view of matching the experimental signals are addressed. The persisting discrepancies are also discussed.